Efficient oxidation of hydrocarbons over nanocrystalline Ce1−xSmxO2 (x = 0–0.1) synthesized using supercritical water1. Issue 56 (19th June 2015) - Pahari, Sandip Kumar; Pal, Provas; Sinhamahapatra, Apurba; Saha, Arka; Santra, Chiranjit; Ghosh, Subhash C.; Chowdhury, Biswajit; Panda, Asit Baran
<x xml:space="preserve">Abstract</x> Highly crystalline cubic Ce1−xSmxO2 (x = 0–0.1) is synthesized using supercritical water, which showed superior catalytic activity for selective oxidation of hydrocarbons.